2019
DOI: 10.3390/v11100953
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Variability Affects CCHFV Detection by RT–PCR: A Tool for In-Silico Evaluation of Molecular Assays

Abstract: The Crimean–Congo hemorrhagic fever virus (CCHFV) is considered to be a major emerging infectious threat, according to the WHO R&D blueprint. A wide range of CCHFV molecular assays have been developed, employing varied primer/probe combinations. The high genetic variability of CCHFV often hampers the efficacy of available molecular tests and can affect their diagnostic potential. Recently, increasing numbers of complete CCHFV genomic sequences have become available, allowing a better appreciation of the genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…When 613 ticks from hunter harvested wild ungulates in South-western Spain in September-December 2017 were screened for CCHFV, different sequences within the genotype Europe V (commonly designated Europe-1) were detected in H. lusitanicum from deer and wild boar and in D. marginatus from wild boar (sequences similar to human isolates from Russia and Iran), probably introduced from eastern Europe. In addition, genotype Africa IV (designated genotype IIIb, Africa-4, according to Gruber et al [ 24 ]) was found in one H. lusitanicum from a deer (similar to an isolate from Nigeria), probably coming from Africa through migratory birds, as previously suggested [ 31 , 41 ]. Curiously, in more than one case, co-feeding CCHFV-infected ticks collected from the same ungulate host exhibited different genotypes [ 37 ].…”
Section: A Touch Of History About Cchf: the Experience In Spainmentioning
confidence: 54%
See 2 more Smart Citations
“…When 613 ticks from hunter harvested wild ungulates in South-western Spain in September-December 2017 were screened for CCHFV, different sequences within the genotype Europe V (commonly designated Europe-1) were detected in H. lusitanicum from deer and wild boar and in D. marginatus from wild boar (sequences similar to human isolates from Russia and Iran), probably introduced from eastern Europe. In addition, genotype Africa IV (designated genotype IIIb, Africa-4, according to Gruber et al [ 24 ]) was found in one H. lusitanicum from a deer (similar to an isolate from Nigeria), probably coming from Africa through migratory birds, as previously suggested [ 31 , 41 ]. Curiously, in more than one case, co-feeding CCHFV-infected ticks collected from the same ungulate host exhibited different genotypes [ 37 ].…”
Section: A Touch Of History About Cchf: the Experience In Spainmentioning
confidence: 54%
“…Based on these data, the reassortant S segment was similar to genotype IV and related to a Nigeria strain that differed from the Asia strains of this genotype. Other authors [ 24 ] had already included this same S sequence from Spain within a new genotype designated IIIb (Africa-4). To reach a consensus about designation of genotypes, genetic linages and groups is a pending challenge.…”
Section: What Is the Potential Future Impact Of Cchf In Western Eumentioning
confidence: 99%
See 1 more Smart Citation
“…ticks in India and China [ 7 , 8 ] has highlighted the need for a more complete genomic dataset in order to better understand the epidemiology of the virus, including viral transmission routes and the extent of re-assortment among genotypes. The potential for such re-assortment is particularly important, as many molecular tests for CCHFV are only capable of detecting a restricted number of closely related genotypes [ 9 ]. It also remains to be seen whether recently reported vaccine candidates, including one based on the S and M segments of the Hoti strain (genotype V) [ 10 ] and another based on the M segment of the IbAr102000 strain (genotype III) [ 11 ], can elicit a protective immune response against viruses belonging to other more distantly related genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The virus is transmitted to humans through a bite from an infected tick or direct contact with infected body fluids of patients. The ixodid tick Hyalomma m. marginatum , plays a major role for the transmission of the disease and it is the natural reservoir of CCHFV 1 4 . CCHF is a neglected disease and re-emerging due to the climate change effecting tick distribution worldwide 5 .…”
Section: Introductionmentioning
confidence: 99%